Indonesian Journal of Obstetric and Gynecology=Majalah Obstetri dan Ginekologi Indonesia, Vol.35 No.4 Halaman 151-244, October 2011 - Perkumpulan Obstetri Dan Ginekologi Indonesia (POGI, 2011)
-Correlation of total antioxidant capacity maesured by ferric reducing ability of plasma (FRAP) assay with the saverity of preeclampsia -The correlation of early initation of breastfeeding with the achievement of exclusive breasfeeding and corresponding factors -Serum magnesium ion content in 31-36 weeks pretem labor patients in Dr. Mohammad Hoesin Hospital Palembang -....